Assignment of Configuration in a Series of Dioxolanone‐Type Secondary Metabolites from Guignardia bidwellii – A Comparison of VCD and ECD Spectroscopy. Issue 26 (26th July 2013) - Andernach, Lars; Sandjo, Louis P.; Liermann, Johannes C.; Buckel, Iris; Thines, Eckhard; Opatz, Till
Abstract: The absolute configurations of a series of phytotoxic dioxolanone‐type secondary metabolites isolated from culture filtrates of the grape black rot fungus Guignardia bidwellii were determined by vibrational circular dichroism (VCD) spectroscopy in the mid‐IR frequency range. Comparison of the recorded data with DFT calculations showed good agreement between experiment and theory for VCD, whereas electronic circular dichroism (ECD) data for the compounds matched poorly with the predicted spectra obtained by time‐dependent DFT (TDDFT) calculations at the same level of theory. Abstract : The absolute configurations of a series of dioxolanone‐type secondary metabolites from Guignardia bidwellii were determined by vibrational circular dichroism (VCD); electronic circular dichroism (ECD) gave ambiguous results.